2014
DOI: 10.1007/s12325-014-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Valsartan/Amlodipine Single-Pill Combination in 11,422 Chinese Patients with Hypertension: an Observational Study

Abstract: IntroductionSingle-pill combination (SPC) therapy of two drugs is recommended by international guidelines, including the Chinese guidelines (2010), for the treatment of hypertension in high-risk patients who require marked blood pressure (BP) reductions. Real-world data on the efficacy and safety of valsartan/amlodipine (Val/Aml) SPC are scarce. The present study is the first observational study in China to evaluate the efficacy (primary endpoint) and safety of Val/Aml (80/5 mg) SPC in Chinese patients with hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…[19] The present analysis of patients from the China Status II study stratified based on 3 stroke subtypes, confirmed the BP-lowering effectiveness and safety of Val/Aml 80/5 mg SPC in Chinese hypertensive patients with hemorrhagic, ischemic, or mixed stroke. The majority of patients achieved BP control, SBP response, and DBP response in all stroke subgroups at the study endpoint at week 8.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…[19] The present analysis of patients from the China Status II study stratified based on 3 stroke subtypes, confirmed the BP-lowering effectiveness and safety of Val/Aml 80/5 mg SPC in Chinese hypertensive patients with hemorrhagic, ischemic, or mixed stroke. The majority of patients achieved BP control, SBP response, and DBP response in all stroke subgroups at the study endpoint at week 8.…”
Section: Discussionsupporting
confidence: 71%
“…[19] The present study is a subanalysis of China Status II, evaluating the effectiveness and safety of 8-week treatment with Val/Aml SPC in hypertensive patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…26 The present study findings of BP reductions with an amlodipine/valsartan in patients previously treated with monotherapy are also similar to those reported in another large observational study in a real-life setting and conducted in Chinese patients. 27 The results of the present study can be used in a generalized large and diverse group of patients suffering from hypertension to whom the drug is prescribed. The results of this study have demonstrated the effectiveness, safety and tolerability of amlodipine/valsartan in patients with hypertension in the general population in a real world settings.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study in older urban community-dwelling Chinese subjects in Shanghai, the antihypertensive drugs used in combination most often were CCBs and ARBs, and FDCs were only used in 12.4% of the younger (65 to 80 years) and 18.2% of the very old (!80 years) subjects with hypertension 9 . The SPC of valsartan/ amlodipine (80/5 mg) was shown to be very effective in lowering BP in the CHINA STATUS II study, a large observational study in China, where the mean reduction in BP was 27.1/ 15.2 mmHg and the combination showed very good tolerability 10 .…”
Section: Single-pill Combinations For Hypertension: First Line Treatmmentioning
confidence: 99%